HEALTH BELIEF MODEL DALAM UPAYA MENINGKATKAN PERILAKU WASPADA STROKE PADA KELOMPOK RISIKO TINGGI DI WILAYAH KERJA PUSKESMAS PONCOKUSUMO KABUPATEN MALANG - Rahmania Ambarika (Universitas STRADA Indonesia, 2016)
The low awareness of stroke risk factors and less familiar symptoms of a stroke ar e major issues on stroke services in Indonesia. Lack of public awareness can slow stroke patients in seeking medical help and impact of delayed treatment of stroke, disability and death. Factors that influence the behavior seen through the stroke vigilance Healt theory Belief Model. The purpose of this study identify factors associated with the alert behavior stroke in high-risk groups to the theoretical approach of the Health Belief Model. This research uses descriptive analytic design with cross sectional approach. Total sample of 144 respondents using purposive sampling technique. The results of the bivariate analysis of correlation between a positive perception of prevention (p value 0.05), negative perceptions of preventive behavior (p value of 0.000). The ability of self-perception is not related to the alert behavior of stroke (p value 0.079). Perceptions of the obstacles associated with the alert behavior stroke (OR 0.338; 95% CI). Negative perceptions or barriers to behavioral change affecting the behavior of vigilance threat deciding stroke